On the loop expansion of the effective action - Phat, Tran Huu; Long, Nguyen Van (Communications in Physics, 2007)
Based on the DeWitt formula the loop expansion of the effective action is easily established. Extending to the system with finite density we develop the in-medium DeWitt formula, which is the starting point for setting up loop expansion of the in-medium effective action.